The Impact of Creatine Supplementation on Strength Training - Janik, Izabela; Kuśmierska, Martyna; Kuśmierski, Jakub (Quality in Sport, 2024)
Introduction: Creatine monohydrate supplementation has become a popular ergogenic aid among athletes and fitness enthusiasts aiming not only to enhance strength and muscle mass but also to augment intense resistance training workouts. This study aims to provide a comprehensive review of the current scientific literature on the effects of creatine supplementation on strength training. What’s more, it contains the mechanisms of action, potential benefits, optimal dosing strategies, and safety considerations associated with creatine supplementation in the context of strength training. Material and Methods of Research: A literature search was conducted on Google Scholar and PubMed using keywords related to the impact of creatine supplementation on strength training. Results: There is no doubt that creatine supplementation has a positive effect on muscle strength, hypertrophy, exercise recovery, performance and power. Creatine also reduces dehydration and cramping, minimizes muscle tightness (including muscle strains and pulls), preventing severe muscle injuries or reducing the severity of muscle injuries. The benefits of supplementing creatine may, in the long run, help athletes achieve bursts of speed and energy, especially during short bouts of high-intensity activities such as weight lifting or sprinting. Conclusion: This study confirms that supplementing with creatine is a reliable and safe approach to bolster strength training results for those aiming to enhance muscular strength, power, and hypertrophy. By increasing intramuscular phosphocreatine levels and aiding muscle protein synthesis, creatine supplementation offers notable advantages in exercise performance and recovery, especially during intense resistance training regimens.